2009
DOI: 10.1128/iai.00700-09
|View full text |Cite
|
Sign up to set email alerts
|

Superior Protective Immunity against Murine Listeriosis by Combined Vaccination with CpG DNA and RecombinantSalmonella entericaSerovar Typhimurium

Abstract: Preexisting antivector immunity can severely compromise the ability of Salmonella enterica serovar Typhimurium live vaccines to induce protective CD8 T-cell frequencies after type III secretion system-mediated heterologous protein translocation in orally immunized mice. To circumvent this problem, we injected CpG DNA admixed to the immunodominant p60 217-225 peptide from Listeria monocytogenes subcutaneously into BALB/c mice and coadministered a p60-translocating Salmonella strain by the orogastric route. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…As expected, no appreciable CD8 ϩ T cell response was detected after DENV PIV-1 vaccination. Vaccine-elicited CD8 ϩ T cell responses have particular requirements for priming, such as proinflammatory conditions that are provided only in the context of viral vector replication (45)(46)(47), the presence of viral nucleic acids (48,49), or specific adjuvants (50). These data therefore suggest that the T cell response induced by PIV-1 vaccination is limited to antigen-specific CD4 ϩ T helper cells which support the production of anti-DENV antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…As expected, no appreciable CD8 ϩ T cell response was detected after DENV PIV-1 vaccination. Vaccine-elicited CD8 ϩ T cell responses have particular requirements for priming, such as proinflammatory conditions that are provided only in the context of viral vector replication (45)(46)(47), the presence of viral nucleic acids (48,49), or specific adjuvants (50). These data therefore suggest that the T cell response induced by PIV-1 vaccination is limited to antigen-specific CD4 ϩ T helper cells which support the production of anti-DENV antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…The data presented here suggest that CSFV-specific IFN-␥-expressing cells may also have cytotoxic capacity and consolidate our previous results where we showed that IFN-␥ expression was restricted to CD8 T cells expressing intracellular perforin (7) and other earlier studies that demonstrated CSFV-specific cytotoxic activity by T cell cultures isolated from vaccinated pigs (8)(9)(10). While IFN-␥-secreting T EM cells have been implicated in protection against a variety of intracellular pathogens, simultaneous production of IFN-␥, TNF-␣, and IL-2 detected at the single-cell level by multiparameter flow cytometry has been correlated with enhanced vaccine-induced protection (45)(46)(47)(48)(49)(50)(51). Moreover, data suggest that such polyfunctional CD8 T memory cells are critical to long-term protection against other viruses belonging to the family Flaviviridae (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, proliferative capacity does not necessarily correlate with protection against infection, since T CMC -like CD8 T cells induced by vaccination with heat-killed L. monocytogenes reveal vigorous proliferation and expansion after challenge with live Listeria , but do not protect against listeriosis as determined by clearance of the bacteria [43]. These findings were supported by a recent study demonstrating that T EMC are more effective than T CMC in conferring protection in the murine Listeria infection model [41], [44]. As mentioned above, the analysis of the kinetics of KDR2-specific CD8 T cell subpopulation formation after SB824 (pHR584) vaccination revealed a clear trend towards the induction of both memory T cell subsets.…”
Section: Discussionmentioning
confidence: 97%